Kynurenine Pathway Metabolites as Potential Biomarkers in Chronic Pain - Andrew Auyeung; Hank C. Wang; Kannan Aravagiri; Nebojsa Nick Knezevic (MDPI AG, 2023)
Chronic pain is a pressing medical and socioeconomic issue worldwide. It is debilitating for individual patients and places a major burden on society in the forms of direct medical costs and lost work productivity. Various biochemical pathways have been explored to explain the pathophysiology of chronic pain in order to identify biomarkers that can potentially serve as both evaluators of and guides for therapeutic effectiveness. The kynurenine pathway has recently been a source of interest due to its suspected role in the development and sustainment of chronic pain conditions. The kynurenine pathway is the primary pathway responsible for the metabolization of tryptophan and generates nicotinamide adenine dinucleotide (NAD+), in addition to the metabolites kynurenine (KYN), kynurenic acid (KA), and quinolinic acid (QA). Dysregulation of this pathway and changes in the ratios of these metabolites have been associated with numerous neurotoxic and inflammatory states, many of which present simultaneously with chronic pain symptoms. While further studies utilizing biomarkers to elucidate the kynurenine pathway's role in chronic pain are needed, the metabolites and receptors involved in its processes nevertheless present researchers with promising sources of novel and personalized disease-modifying treatments.